Paralleling the Quality and Economy of Levofloxacin Hemihydrate and Cefuroxime Axetil Tablets - Pawar, Atmaram; Chainpure, Mahesh; Dhapte-Pawar, Vividha (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim/Background: The Government of India has initiated different regulations and provisions to provide low cost medicines at affordable rates than the high cost medicines. The government has initiated Jan Aushadhi stores in every city and village of India with the motto of promoting quality medicines for all at economic price. Improving the public perception and addressing their doubts regarding the quality and efficacy of low-cost medicines is a big challenge in this endeavour. Materials and Methods: In the present study, we have compared the low, medium and high cost medicines of biopharmaceutical classification system class I drug, levofloxacin hemihydrate and biopharmaceutical classification system class II drug, cefuroxime axetil, in order to verify their quality and efficacy. Existing low cost and medium cost brands of these drugs were selected and compared with their respective high cost products as per quality standards of Indian Pharmacopoeia viz. weight variation, friability, disintegration, assay and in vitro dissolution study specified in general and individual monographs. Moreover, ex vivo permeability and antimicrobial activities were assessed while comparing the efficacy of these products. Results: Findings from these studies revealed no significant differences between the efficacy of low cost, medium cost and high cost products. All products complied with the Indian Pharmacopoeia tests along with the comparable ex vivo permeation and antimicrobial activities for both the drugs. Conclusion: This study revealed that the low cost and medium cost tablets of levofloxacin hemihydrate and cefuroxime axetil can be used at par with the costlier tablets of same drugs.
Keywords: Levofloxacin hemihydrate; Cefuroxime axetil; Generic; Microbial assay; Pharmacopoeial evaluation